First discovery of the spinicaudatan genus Carapacestheria Shen, 1994 in Asia - Li, Gang (Paleontological Research, 2023)
The rare clam shrimp (spinicaudatan) genus Carapacestheria Shen, 1994 was originally described from the upper Lower-lower Middle Jurassic of Antarctica. Later, it was reported from the Middle Jurassic of Argentina and the lowest Cretaceous of the United Kingdom. Here, a new species, Carapacestheria cangshanensis sp. nov., is described from the Upper Jurassic Penglaizhen Formation in southwestern China. The subquadrate-shaped carapace of the new species has a distinct ornamentation pattern, which transitions from medium-sized reticulations to radial lirae. There are punctae within the polygonal cells and between the lirae. According to its geological range and geographical distribution, Carapacestheria first occurred in Antarctica, and later appeared in the northern hemisphere during the Late Jurassic.